Export entry, export exit, and productivity in German manufacturing industries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2007)
This paper contributes to the flourishing literature on exports and productivity by using a unique newly available panel of exporting establishments from the manufacturing sector of Germany from 1995 to 2004 to test three hypotheses derived from a theoretical model by Hopenhayn (Econometrica 1992): (H1) Firms that stop exporting in year t were in t-1 less productive than firms that continue to export in t. (H2) Firms that start to export in year t are less productive than firms that export both in year t-1 and in year t. (H3) Firms from a cohort of export starters that still export in the last year of the panel were more productive in the start year than firms from the same cohort that stopped to export in between. While results for West Germany support all three hypotheses, this is only the case for (H1) and (H2) in East Germany.
Keywords: F14; L60; 330; Exportindustrie; Verarbeitendes Gewerbe; Internationale Markteintrittsstrategie; Marktaustritt; Produktivität; Deutschland; Neue Bundesländer